{Lateral Termination of a Cycladic-Style Detachment System (Hymittos, Greece)} - Coleman, M. J.; Schneider, D.A.; Grasemann, B.; Soukis, K.; Lozios, S.; Hollinetz, M. S. (Tectonics, 2020)
The bedrock of Hymittos, Attic peninsula, Greece, exposes a pair of low-angle crustal-scale ductile-then-brittle detachment faults. The uppermost detachment fault separates sub-greenschist facies phyllite and marble of a Pelagonian Zone hanging wall, from greenschist facies metasedimentary schist, calc-schist, and marble correlated to the Cycladic Blueschist Unit. A second, structurally lower detachment fault subdivides the metamorphic rocks of the Cycladic blueschist unit footwall into middle and lower units. There is a marked step in metamorphic grade between the sub-greenschist facies uppermost package, and the middle-to-upper greenschist facies middle and lower packages. A suite of new white mica 40Ar/39Ar and zircon (U-Th)/He dates indicates accommodation of deformation along these faults occurred from the late Oligocene to the late Miocene with both faults active during the middle Miocene. The structures have clear top-S/SSW kinematics determined from flanking folds, sigmoids, shear bands, stair-stepping of strain shadows on porphyroclasts, and SCC' fabrics. The ductile-to-brittle deformation of the structures, morphology of the massif, and the increase in metamorphic grade suggest these low-angle structures are part of a major, crustal-scale extensional complex, located at the northwest end of the West Cycladic Detachment System, that accommodated Miocene bivergent exhumation of Attic-Cycladic metamorphic core complexes in the central Aegean. Taken together, the above data suggest that multiple coeval detachment branches may form in areas with high strain gradients to accommodate the mechanically necessary termination of Cycladic-style detachment systems.
Keywords: Cyclades; fault architecture; geochronology; low-angle detachment faults; white mica 40Ar/39Ar; zircon (U-Th)/He